Safety, biodistribution and radiation dosimetry of 18 F-rhPSMA-7.3 in healthy adult volunteers - Tolvanen Tuula; Kalliokoski Kari; Malaspina Simona; Kuisma Anna; Lahdenpohja Salla; Postema Ernst J.; Miller Matthew P.; Scheinin Mika (Society of Nuclear Medicine and Molecular Imaging, 2022)
This first-in-human study investigated the safety, biodistribution and radiation dosimetry of the novel 18F-labeled radiohybrid prostate-specific membrane antigen (rhPSMA) positron emission tomography (PET) imaging agent, 18F-rhPSMA-7.3. Methods: Six healthy volunteer subjects (3 males, 3 females) underwent multiple whole-body PET acquisitions at scheduled time points up to 248 minutes after the administration of 18F-rhPSMA-7.3 (mean activity 220; range, 210-228 MBq). PET scans were conducted in three separate sessions and subjects were encouraged to void between sessions. Blood and urine samples were collected for up to 4 hours post-injection to assess metabolite-corrected radioactivity in whole blood, plasma and urine. Quantitative measurements of 18F radioactivity in volumes of interest (VOIs) over target organs were determined directly from the PET images at 8 time points and normalized time-activity concentration curves were generated. These normalized cumulated activities were then inputted into the OLINDA/EXM package to calculate the internal radiation dosimetry and the subjects' effective dose. Results: 18F-rhPSMA-7.3 was well tolerated. One adverse event (mild headache, not requiring medication) was considered possibly related to 18F-rhPSMA-7.3: because of the temporal association with 18F-rhPSMA-7.3 injection, a causal relationship could not be excluded. The calculated effective dose was 0.0141 mSv/MBq when using a 3.5-hour voiding interval. The organs with the highest absorbed dose per unit of administered radioactivity were the adrenals (mean absorbed dose, 0.1835 mSv/MBq), the kidneys (mean absorbed dose, 0.1722 mSv/MBq), the submandibular glands (mean absorbed dose, 0.1479 mSv) and the parotid glands (mean absorbed dose, 0.1137 mSv/MBq). At the end of the first scanning session (mean time, 111 min post-injection), an average of 7.2% (range, 4.4-9.0%) of the injected radioactivity of 18F-rhPSMA-7.3 was excreted into urine. Conclusion: The safety, biodistribution and internal radiation dosimetry 18F-rhPSMA-7.3 are considered favorable for PET imaging.